High-Fat-Diet-Induced Oxidative Stress in Giant Freshwater Prawn (Macrobrachium rosenbergii) via NF-κB/NO Signal Pathway and the Amelioration of Vitamin E - Cunxin Sun; Fan Shan; Mingyang Liu; Bo Liu; Qunlan Zhou; Xiaochuan Zheng; Xiaodi Xu (MDPI AG, 2022)
Lipids work as essential energy sources for organisms. However, prawns fed on high-fat diets suffer from oxidative stress, whose potential mechanisms are poorly understood. The present study aimed to explore the regulation mechanism of oxidative stress induced by high fat and the amelioration by vitamin E (VE) of oxidative stress. Macrobrachium rosenbergii were fed with two dietary fat levels (LF 9% and HF 13%) and two VE levels (200 mg/kg and 600 mg/kg) for 8 weeks. The results showed that the HF diet decreased the growth performance, survival rate and antioxidant capacity of M. rosenbergii, as well as inducing hypertrophied lipid droplets, lipophagy and apoptosis. A total of 600 mg/kg of VE in the HF diet alleviated the negative effects induced by HF. In addition, the HF diet suppressed the expression of toll-dorsal and imd-relish signal pathways. After the relish and dorsal pathways were knocked down, the downstream iNOS and NO levels decreased and the MDA level increased. The results indicated that M. rosenbergii fed with a high-fat diet could cause oxidative damage. Its molecular mechanism may be attributed to the fact that high fat suppresses the NF-κB/NO signaling pathway mediating pro-oxidant and antioxidant targets for regulation of oxidative stress. Dietary VE in an HF diet alleviated hepatopancreas oxidative stress and apoptosis.